Bimetallic Ni–Co selenide heterostructure aerogel for highly efficient overall water splitting. (15th February 2023) - Liu, Hongchen; Yang, Fan; Chen, Fengjiang; Che, Sai; Chen, Neng; Xu, Chong; Wu, Ni; Wei, Wenkai; Li, Yongfeng
Abstract : A high-performance NiSe2 –CoSe2 aerogel was prepared via facile gelation and selenium vapor deposition for efficient water splitting. Its heterostructure and aerogel morphology provided high intrinsic activity and abundant active sites, respectively. Abstract : Exploring transition metal-based electrocatalysts with excellent performance toward alkaline overall water splitting is of significant importance for the hydrogen economy but remains challenging. Herein, we designed and prepared a bimetallic Ni–Co selenide heterostructure aerogel (NiSe2 –CoSe2 ) for highly efficient overall water splitting via facile spontaneous gelation and selenium vapor deposition. The optimized sample exhibited extremely low overpotentials of 65/220 mV for the HER/OER at a geometric current density of 10 mA cm −2 in 1 M KOH electrolyte. Assembled as an electrolyzer for overall water splitting, NiSe2 –CoSe2 only required a low cell voltage of 1.56 V to achieve 10 mA cm −2 with decent stability, which was comparable to those of commercial noble-metal catalysts (Pt/C + RuO2 ). The exceptional performance was attributed to the unique porous morphology of the aerogel with abundant active sites and the bimetallic selenide heterostructure with excellent intrinsic activity. Density functional theory (DFT) calculations further revealed the ideal adsorption performance for reactant intermediates at the heterogeneous phase boundaries. This work provides an anticipated perspective of transition metal selenide bifunctional electrocatalysts for overall water splitting.